Phytochemical Constituents and Biological Activity Studies of the Stem of Dichapetalum Madagascariense - Appiah, A.M. (University of Ghana, 2013)
This investigation examined petroleum ether, acetone/chloroform, and ethanol extracts of the whole stem of Dichapetalum madagascariense Poir. The petroleum ether extract afforded epifriedelanol (friedelan-3β-ol) together with two mixtures- friedelan-3-one and friedelan-3β-ol; and β-sitosterol and stigmasterol. The acetone/chloroform extract (obtained by combining the acetone and chloroform extracts) afforded friedelin (friedelan-3-one) and β-sitosterol but showed dichapetalin A on TLC. The ethanol extract afforded the previously isolated mixture of friedelan- 3-one and friedelan-3β-ol. All isolated compounds were identified by comparison of melting points, Retardation factor (R f ) from TLCs, IRs, and 1 H- and 13 C NMR spectroscopy. Biological activities involving insecticidal and anthelminthic properties were carried out on the extracts and the isolates. The insecticidal activity investigated the toxicity and grain protectant potential of different extracts and isolates of the plant against Sitophilus zeamais in the laboratory using contact toxicity, progeny production and damage assessment assays. The less polar extracts, for example petroleum ether extract, recorded lower LD 50 value of 0.86 μg/μl after 48hour exposure. Friedelan-3-one, friedelan-3β-ol, and a mixture of friedelan-3-one and friedelan-3β-ol recorded LD 50 values of 0.48, 0.56 and 0.52 μg/μl respectively following 48hour exposure against Sitophilus zeamais. The different extracts caused significant reduction in feeding damage, number of F1 progeny produced, and inhibition of the development of eggs and immature stages of Sitophilus zeamais. There was complete protection of grains by the different extracts applied at the highest dosage of 10 g per 100g of grain. The anthelminthic activity using the Egg Hatch Assay (EHA) saw friedelan-3β-ol recording the lowest IC 50 value of 0.64 μg/μl but a mixture of β- sitosterol and stigmasterol had the largest IC 50 value of 9.41 μg/μl in inhibiting the hatching of Necator americanus eggs. Based on the IC 50 values, friedelan-3β-ol, friedelan-3-one and β- sitosterol exhibited similar potency. However, no test sample had > 90% inhibition as recommended by WHO but β-sitosterol and friedelan-3β-ol appeared to have significant values > 50%. D. madagascariense exhibited some amount of insecticidal and anthelminthic properties and so under practical conditions, relatively higher doses may be required as compared to doses applied in the laboratory experiment.
Thesis (MPHIL) - University of Ghana, 2013